Pengaruh Brand Awareness, Brand Association, dan Perceived Quality terhadap Keputusan Pembelian Produk Iphone dari Apple di Kota Madya Yogyakarta - Guptagama Suharmawan Lingga; Muinah Fadhilahi; Agus Dwi Cahya (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2023)
This study aims to examine the effect of Brand Awareness, Brand Association, and Perceived Quality on increasing purchasing decisions. This research is a quantitative research. The sample for this study was collected using a method called purposive sampling. Based on the purposive sampling technique, data collection was carried out through an online survey using the Google Forms platform, with a total sample of 100 people from the population of Yogyakarta City. Multiple linear regression using SPSS version 25 is the data analysis technique used. The findings of this study indicate that the Brand Awareness factor (X 1) has no effect on purchasing decisions (Y). Variable social brand associations (X 2) have an impact on purchasing decisions (Y). Then the Perceived Quality (X3) variable has a beneficial and significant influence on buying choices. Keywords: Brand Awareness, Brand Association, Perceived Quality, Purchase Decision